Teacher Mastery of Thematic Learning in Lower Grades at Madrasah Ibtidaiyah - Siti Nur Hidayah (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
This study aims to: (1) examine teacher mastery of thematic learning in lower grades at MI Salafiyah Kutukan; (2) identify the obstacles faced by teachers in the process of thematic learning in lower grades at MI Salafiyah Kutukan; and (3) describe the efforts made by teachers to improve the thematic learning process in lower grades at MI Salafiyah Kutukan. This research is a descriptive qualitative study with data sources consisting of lower-grade thematic teachers at MI Salafiyah Kutukan. Data were collected through observation, interviews, and documentation techniques. The research instruments used were observation guidelines, in-depth interview guidelines, and documentation guidelines. Data analysis was conducted through three stages: data reduction, data presentation, and drawing conclusions. The results of the qualitative descriptive analysis indicate that teacher mastery of thematic learning has not been well mastered and implemented by teachers at the school. The obstacles faced by teachers in the thematic learning process include a lack of ability to integrate subjects thematically, limited variation in learning methods, and insufficient classroom management skills. The efforts made by teachers to improve the thematic learning process include providing learning media and teaching aids, as well as participating in thematic learning training organized by the education office and socialization activities conducted by the school principal.